Kemunduran Demokrasi di Asia Tenggara: Analisis Fenomena Authoritarian Backsliding di Indonesia dan Thailand - Ria Amelia; Elly Nurlia; Amealiea Prihatiningsih Malandy's; Azalia Salsabila; Siti Alya Aryanti (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study aims to analyze the phenomenon of authoritarian backsliding or democratic regression in Southeast Asia, focusing on Indonesia and Thailand. Conceptually, backsliding refers to the gradual weakening of democracy through formal and legal mechanisms by political actors within the system itself. The research employs a literature study method, analyzing academic sources and international reports relevant to the topic. The findings indicate that both Indonesia and Thailand have experienced democratic decline characterized by the consolidation of executive power, the weakening of oversight institutions, and restrictions on civil liberties. In Indonesia, democratic regression occurs primarily through executive aggrandizement and strategic manipulation of elections, while in Thailand, it manifests through promissory coups under military dominance. The study concludes that democratic decline in Southeast Asia often occurs not through overt authoritarian takeovers but through a subtle erosion of democratic institutions that undermines popular sovereignty.